The Role of IT Trust Related to the Impact of Technostress on User Performance of the SAKTI - Kartika Ayuning Tiar; Sriwidharmanely Sriwidharmanely (Fakultas Ekonomi Dan Bisnis, Universitas Bengkulu, 2023)
This research endeavors to broaden the understanding of trust as a coping mechanism rooted in emotions, specifically concerning technostress experienced by SAKTI users. The study explores how trust impacts individuals' performance in this context. The objective of this research is to investigate the correlation between Technostress, IT Trust, and the performance of users of the SAKTI system. This study makes a scholarly contribution to systems and technologies by examining their impact on application users' experiences, specifically focusing on their usage patterns and the resulting positive or bad experiences. The present study used a questionnaire survey methodology to collect primary data. This study demonstrates no detrimental impact of technostress on the performance of SAKTI users. The findings of this study indicate that the mediating role of IT Trust is evident in the association between technostress and the performance of SAKTI users. Engaging in proactive measures to alleviate the technical stress encountered by SAKTI is deemed permissible due to its potential impact. For users of SAKTI, the presence of technology is not to be taken lightly; rather, it catalyzes enhancing personal performance. The presence of confidence in technology can mitigate the effects of technological stress and foster positive engagement among SAKTI users.